Comprehensive analysis to identify a novel diagnostic marker of lung adenocarcinoma and its immune infiltration landscape - Zhu, Ankang; Pei, Dongchen; Zong, Yan; Fan, Yan; Wei, Shuai; Xing, Zhisong; Song, Shuailin; Wang, Xin; Gao, Xingcai (Frontiers in Oncology, 2023)
Background:Lung cancer is still a problem facing all mankind. It is the cancer with the highest morbidity and mortality in the world, and the most common histological type of lung cancer is lung adenocarcinoma (LUAD), accounting for about 40% of lung malignant tumors.This study was conducted to discuss and explore the biomarkers and immune-related pathways during the development and progression of LUAD and their relationship with immune cell infiltration. Results:8482 differential genes were selected. The turquoise module with the highest correlation with LUAD was identified among the 7 modules obtained with WGCNA. After lasso analysis, 12 HUB genes were selected as possible biomarkers for LUAD.According to the immune infiltration results，CD4 + T cells, B cells, and NK cells were high in LUAD sample tissue. The ROC curve showed that all of these 12 HUB genes had a high diagnostic value. Finally, the functional enrichment analysis suggested that the HUB gene is mainly related to the inflammatory response and the immune response.According to RT-qPCR study,we found that the expression of DPYSL2, OCIAD2 and FABP 4 in A549 lung cancer cells was both higher than normal cells and statistically significant. The expression content of DPYSL2 was lower in H1299 cells than in normal lung epithelial cells. However, the expression difference of FABP 4 and OCIAD2 genes in H1299 lung cancer cells was not significant, but both showed a trend of increase. Conclusion:The pathogenesis and progression mechanism of LUAD are closely related to T cells, B cells, and monocytes.12 HUB genes(ADAMTS8,CD36,DPYSL2,FABP4,FGFR4,HBA2,OCIAD2,PARP1,PLEKHH2,STX11,TCF21,TNNC1) may participate in the progression of LUAD through immune-related signaling pathways.